SOSIALISASI LITERASI KEUANGAN DALAM MENDUKUNG PENGELOLAAN FINANSIAL UMKM DAN PENGELOLAAN KEUANGAN RUMAH TANGGA PADA KABUPATEN SIAK - Desmiyawati, Desmiyawati; Khoiriyah, Mayla; Ramaiyanti, Sinta; Humairoh, Fitri (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2024)
This community service activity aims to enhance financial literacy among MSMEs (Micro, Small, and Medium Enterprises) actors in Siak Regency, focusing on MSMEs financial management and household financial management. The activity involved socialization and training sessions that included theoretical explanations, practical examples, and interactive discussions on financial literacy, funding, lending, and the application of financial technology (fintech). The team, comprising lecturers and students from the Faculty of Economics and Business at Universitas Riau, employed lecture and discussion methods to deliver the material, followed by participant evaluations to assess their understanding before and after the sessions. Results indicate significant improvement in participants’ knowledge of financial literacy and financial reporting based on SAK EMKM standards. This initiative is expected to assist MSMEs in better financial management, expanding credit access, and supporting sustainable business growth.